PRZEFORMUŁOWANIE JAKO NARZĘDZIE BADAWCZE W AKWIZYCJI JĘZYKA I GLOTTODYDAKTYCE - Karpińska-Szaj, Katarzyna; Wojciechowska, Bernadeta (Neofilolog, 2018)
The subject of this article is the use of reformulation, the instrument of language acquisition research, in studies on language teaching and learning. Incorporating reformulation into the methodological repertoire of language education research requires a clear definition of differences in the subject-matter and in objectives of research between the two disciplines, in order to clearly capture the potential and limitations of this tool. This article will consider the innovative potential of reformulation at both the research level and the didactic level, at various stages of development of communicative competencies in a foreign language.